External Responsiveness of the SuperOpTM Device to Assess Recovery After Exercise: A Pilot Study - Ardigò, Luca Paolo; Palermi, Stefano; Padulo, Johnny; Dhahbi, Wissem; Russo, Luca; Linetti, Simone; Cular, Drazen; Tomljanovic, Mario (Frontiers in Sports and Active Living, 2020)
Post-exercise recovery is a complex process involving a return of performance and a physiological or perceptual feeling close to pre-exercise status. The hypothesis of this study is that the device investigated here is effective in evaluating the recovery state of professional cyclists in order to plan effective training. Ten professional male cyclists belonging to the same team were enrolled in this study. Participants performed a seven-day exercise program (D1, D4, and D7: low intensity training; D2 and D5: passive recovery; D3: maximum oxygen consumption [VO2Max] test [for maximum mechanical power assessment only]; and D6: constant load test). During the week of monitoring, each morning before getting up, the device assessed each participant’s so-called Organic Readiness (OR [a.u.]), based on blood-pressure, heart-rate, features of past exercise session and following self-perceived condition. Based on its readings and algorithm, the device graphically displayed four different colours/values, indicating general exercise recommendations: green/3=“you can train hard”, yellow/2=“you can train averagely”, orange/1=“you can train lightly”, or red/0=“you should recover passively”. During the week of research, morning OR values and Bonferroni post-hoc comparisons showed significant differences between days and namely values 1) D2 (after low intensity training) was higher than D4 (after VO2Max test; P=0.033 and d=1.296) and 2) D3 and D6 (after passive recovery) were higher than D4 (after VO2Max test; P=0.006 and d=2.519) and D5 (after low intensity training; P=0.033 and d=1.341). The receiver operating characteristic analysis area under curve recorded a result of 0.727 and could differentiate between D3 and D4 with a sensitivity and a specificity of 80%. Preliminarily, the device investigated is a sufficiently effective and sensitive/specific device to assess the recovery state of athletes in order to plan effective training.